Introduction to the situation of the goat sector in the Murcia region (Spain) - Navarro M.J.; Fernández C. (Analyse technico-économique des systèmes de production ovine et caprine : méthodologie et valorisation pour le développement et la prospective., 2006)
This study aims to make an analysis of the most important characteristics of the goat sector in the region of Murcia so as to carry out a diagnosis of the present situation and in turn reflect on the possible steps to be taken for its improvement. The data was analysed through descriptive statistics. Ninety-five surveys were carried out following random stratified criteria. The average size of the herd is 200 female. The breed is predominantly Murciano-Granadina. The sale of milk, followed by the sale of kids are the main source of income in the dairy farms and very few livestock farmers gain income from reproduction sales (4.2%). The average age of farmers is 47 years. An increase in the use of milk control is considered a useful tool for improving a considerable number of key aspects in the profitability of the farms, as are a pure breed livestock and improvements in feeding.
Séminaire du sous-réseau Systèmes de Production du réseau Interrégional FAO-CIHEAM de recherche et développement sur les ovins et caprins, 2005/06/16-18, Seville (Spain)